Penerapan Model Pembelajaran Multilierasi Informasi Untuk Meningkatkan Pemahaman Konsep Jual Beli - Budi Febriyanto; Ari Yanto (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
This article aimed to improve the understanding of the concept of purchase and sale in class III Elementary School of Mekarjaya III through the application of information multiliterasi learning models. This research was classroom action research. This research was conducted in three cycles. The results showed that the percentage of classical completeness in the first cycle has average 63.2 with the percentage of classical completeness which was 48.5%. In the second cycle the average score of students were 70 with the percentage of classical completeness 63.6%. In the third cycle the average value of students were 81.2 with the percentage of classical completeness 87.9%. Then it can be concluded that the application of the multiliteration learning model of information on social studies subjects has success to increase the understanding of the concept purchase and sale in class III Elementary School of Mekarjaya III District Majalengka. Key words: Multiliteration Information Model, Understanding of Purchase and Sale